Ralph Izard family papers - Izard, Ralph, 1742-1804.
Correspondence and miscellaneous material. Includes correspondence of Ralph Izard relating to his Charleston, S.C., estate and the education of his son, George Izard; and correspondence of Ralph Izard, Jr., relating in part to his service with the U.S. Navy during the Tripolitan War. Also includes correspondence of Ralph Izard's wife, Alice DeLancey Izard; their daughter, Margaret Izard Manigault; and Ralph Izard, Jr.'s wife, Elizabeth Middleton Izard, relating to family matters and social affairs in Charleston, S.C., and Philadelphia, Pa. Other correspondents include Thomas Pinckney and John Parker.
Microfilm edition available
Microfilm produced from originals in the Manuscript Division.
Delegate to the U.S. Continental Congress and U.S. senator from South Carolina and diplomat.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Izard, Alice DeLancey, -- 1745-1832 -- Correspondence; Izard, Elizabeth Middleton, -- 1787-1822 -- Correspondence; Izard, George, -- 1777-1828.; Izard, Ralph, -- 1785-1824 -- Correspondence; Manigault, Margaret Izard, -- 1768-1824 -- Correspondence; Parker, John, -- 1759-1832 -- Correspondence; Pinckney, Thomas, -- 1750-1828 -- Correspondence; Izard family; United States. -- Navy -- History -- Tripolitan War, 1801-1805.; Charleston (S.C.) -- Social life and customs; Pennsylvania -- Social life and customs; Philadelphia (Pa.) -- Social life and customs; South Carolina -- Social life and customs; United States -- History -- Tripolitan War, 1801-1805.; Delegates, U.S. Continental Congress -- South Carolina; Diplomats; Senators, U.S. Congress -- South Carolina